2015
DOI: 10.19128/turje.181070
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes of Pre-service Teachers towards Teaching Profession

Abstract: This study examined pre-service mathematics teachers' attitudes towards teaching profession and explored the impact of gender and grade level on their attitudes. Participants consisted of 162 pre-service teachers, enrolled in elementary mathematics education program at a middle sized public university located in the Mediterranean region of Turkey. Data were collected during the fall semester of 2012-2013 academic years, from four different grade levels. As the data collection instrument 'Attitude Scale towards… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 3 publications
1
12
0
5
Order By: Relevance
“…The differences between means of females and males are statistically significant for the overall scale of teaching efficacy, efficacy for student engagement, efficacy for instructional strategies, and attitude scale towards the teaching profession. Some of the researchers found a significant difference in teacher efficacy (Fives & Looney, 2009) and in attitudes toward teaching (Çapri & Çelikkaleli, 2008;Çaycı, 2011;Fadlelmula, 2013) in favour of females, consistently with this study. A few researchers found that males feel more efficacious (Demirtaş et al, 2011;Tran, 2015) and have more positive attitudes (Parylo et al, 2015).…”
Section: Discussionsupporting
confidence: 86%
“…The differences between means of females and males are statistically significant for the overall scale of teaching efficacy, efficacy for student engagement, efficacy for instructional strategies, and attitude scale towards the teaching profession. Some of the researchers found a significant difference in teacher efficacy (Fives & Looney, 2009) and in attitudes toward teaching (Çapri & Çelikkaleli, 2008;Çaycı, 2011;Fadlelmula, 2013) in favour of females, consistently with this study. A few researchers found that males feel more efficacious (Demirtaş et al, 2011;Tran, 2015) and have more positive attitudes (Parylo et al, 2015).…”
Section: Discussionsupporting
confidence: 86%
“…According to the Z test performed to determine the significance of the Hedges g values calculated according to the random effect model, it can be said that the difference in effect size was significant since p <0.05 was found in 19 studies (Baykara Pehlivan, 2010; Pektaş and Kamer, 2011;Tümkaya, 2011;Aydın and Sağlam, 2012;Gökçe and Sezer, 2012;Gür Erdoğan and Zafer Güneş, 2012;Kızıltaş et al, 2012;Aydın and Tekneci, 2013;Çağlar, 2013;İpek et al, 2015;Karatekin et al, 2015;İlter and Köksalan, 2011;Uğurlu and Polat, 2011), but because it was p> Korkmaz and Usta, 2010;Kayan-Fadlelmula, 2013;Kahyaoğlu et al, 2013;Tanel and Tanel, 2013;Tunçeli, 2013;Akgün and Özgür, 2014;Taşdemir, 2014;Dinçer and Yılmaz, 2015;Kesen and Polat, 2014), it was not statistically significant. The z-test calculations performed to determine the statistical significance of the effect size in the random effect model were found to be z = 6,336 and p = 0,000.…”
Section: Resultsmentioning
confidence: 89%
“…It has been determined that there are many studies positive and high in evaluating the prospective teachers' attitudes in general (Akpınar et al, 2006;Çetinkaya, 2009;Andronache et al, 2014;Kayan Fadlelmula, 2013;Caglar, 2013;Baykara Pehlivan, 2008;Baykara Pehlivan, 2010;Akbulut and Karakus, 2011). It is seen that high attitudes of prospective teachers will provide professional satisfaction (Taşdemir, 2014) and promising in terms of the teaching profession (Kesen and Polat, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…It was determined that there was a significant correlation between pre-service teachers' self-efficacy beliefs and their attitudes towards the teaching profession (Ekici, Çıbık & Fettahlıoğlu, 2014;Demirtaş, Cömert & Özer, 2011). Based on the results of certain studies (Fadlelmula, 2013;Terzi & Tezci, 2007), it was determined that female pre-service teachers had more positive attitudes towards the teaching profession when compared to male pre-service teachers, in certain others (Demirtaş & Aksoy, 2015;Demirtas, Cömert & Özer, 2011), it was found that there was no significant difference between female and male teachers' attitudes towards the profession. It was observed that there was a significant difference between the attitudes of pre-service teachers who choose the teaching profession for internal reasons and the attitudes of pre-service teachers who choose the teaching profession for external reasons in a study conducted by Üstüner, Demirtaş & Cömert (2009).…”
Section: Conscientiousnessmentioning
confidence: 99%